Analysis of Work Environment on Employee Performance with Work Motivation as Intervening Variable at PT. Socfindo - Handayani Harahap, Hastuti; Sitindaon, Nikson; Zurlaini Damanik, Ayu; Khairawati, Khairawati; Fuadi, Fuadi (PT. Radja Intercontinental Publishing, 2022)
This study aims to determine the analysis of the work environment on employee performance with work motivation as an intervening variable at PT. SOCFINDO. The researcher uses a descriptive quantitative approach. Replication research is the repetition of the basic experiment. The analytical method used is multiple linear regression model. As for the results of this study, the first hypothesis proposed states that the work environment variable (X) has an effect on the work motivation variable (Z). Work Environment variable (X) has no effect on Employee Performance variable (Y). Work Motivation variable (Z) has an effect on Employee Performance variable (Y). work environment variables cannot mediate the effect of work environment on work motivation. So it can be proven that H4 is rejected. The results of the study indicate that the role of work motivation on employee performance is significant, at PT. Socfindo means that employee motivation affects the way employees show their daily work performance. Health facilities and insurance in this case have met the basic needs of employees in the category of security needs.